2018
DOI: 10.1002/bmc.4208
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic analysis for the protective effects of mangiferin on sepsis‐induced lung injury in mice

Abstract: This study aimed to investigate the efficacy of mangiferin, including its known antioxidant and anti-inflammatory effects on sepsis-induced lung injury induced by a classical cecal ligation and puncture (CLP) models in mouse using a metabolomics approach. A total of 24 mice were randomly divided into four groups: the sham group was given saline before sham operation. The CLP group received the CLP operation only. HMF and LMF groups were given mangiferin treatment of high dose and low dose of mangiferin, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
2
5
0
Order By: Relevance
“…Metabolic changes in the lung after cecal ligation and puncture sepsis have been reported to include alterations in amino acid metabolism, purine metabolism, lipid metabolism, and energy regulation. 92 Metabolites identified in the lung with the present study are involved with aminoacyl-tRNA biosynthesis, valine/leucine/isoleucine biosynthesis, alanine/aspartate/glutamate metabolism, and pantothenate and CoA biosynthesis, including significantly increased valine, alanine, isoleucine, leucine, and threonine and significantly decreased aspartic acid (Figure 5D). In addition, metabolites involved in arginine and proline metabolism included significantly increased fumaric acid, urea, and putrescine and significantly decreased aspartic acid (Figure 5D).…”
Section: Lungsupporting
confidence: 50%
See 1 more Smart Citation
“…Metabolic changes in the lung after cecal ligation and puncture sepsis have been reported to include alterations in amino acid metabolism, purine metabolism, lipid metabolism, and energy regulation. 92 Metabolites identified in the lung with the present study are involved with aminoacyl-tRNA biosynthesis, valine/leucine/isoleucine biosynthesis, alanine/aspartate/glutamate metabolism, and pantothenate and CoA biosynthesis, including significantly increased valine, alanine, isoleucine, leucine, and threonine and significantly decreased aspartic acid (Figure 5D). In addition, metabolites involved in arginine and proline metabolism included significantly increased fumaric acid, urea, and putrescine and significantly decreased aspartic acid (Figure 5D).…”
Section: Lungsupporting
confidence: 50%
“…In addition, metabolites involved in arginine and proline metabolism included significantly increased fumaric acid, urea, and putrescine and significantly decreased aspartic acid (Figure 5D). The significant alterations identified in the present study did not overlap with those in the previous mouse study 92 and may represent differences in the timing of the sepsis (18 hours versus 1 week), the model used (pig versus mouse), or the infection (i.v. P. aeruginosa versus cecal ligation and puncture).…”
Section: Lungsupporting
confidence: 42%
“…Dysregulation of pro-inflammatory cytokines trigger a cytokine storm that may result in tissue damage and organ dysfunction (29). Due to its structural characteristics, lung is the primary failing organ of systemic inflammatory response syndrome (SIRS) (30). Lung injury in septic mice was characterized by alveolar septal thickening, extensive edema, massive infiltration of inflammatory cells, and alveolar congestion/collapse.…”
Section: Sgc-cbp30 Alleviated Tissue Damage In Sepsis Modelmentioning
confidence: 99%
“…Moreover, adipose tissue-derived mesenchymal stem cells can suppress the inflammatory responses in the lungs of septic rats by regulating the levels of acetylcholine, spermine, phenylalanine, and threonine (Cui J. et al, 2020). Furthermore, mangiferin can improve lung injury caused by sepsis by inhibiting oxidative stress and regulating the lipid metabolism and energy biosynthesis (Wang et al, 2018;Xu et al, 2020 Lophatheri herba], and can be used for treating the early stage of sepsis. Clinical study revealed that combination treatment of LG and western therapy could significantly suppress the inflammatory response and reduce platelet activation/thrombocytopenia in spetic petients (Wang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%